METHOD FOR HARVESTING SOLAR ENERGY - Bassi, Hussain (Journal of Applied Engineering Science, 2021)
The cooling of the surface of the solar photovoltaic (PV) system is a major operative factor in achieving greater efficiency. Correct cooling can improve electrical efficiency and reduce cell degradation rates over time. This results in increasing the life of the solar PV modules. In industrial and domestic utilization, the cooling system is used for the removal of excess heat. This paper presents a new method for cooling systems for solar PV. The additional feature of the method has been the tracking of sunlight for efficient power generation. Further, the extra heat can be utilized for other purposes including heating and power generation through thermal means. The concept of the proposed system has been explained in detail with the pictorial representation. Also, for the validation of the improved performance of the proposed system, a detailed comparison with the conventional methods have been provided for five different cities of Saudi Arabia. The proposed system shows improved performance for all operating conditions.
Keywords: solar PV system; solar cooling; photovoltaic; energy harvesting; solar energy